Outline Report of the Study Group on Educated Unemployed - Planning Commission (Planning Commission, 1956)
The Study Group on Educated Unemployed—hereafter referred to as the Group was set up in the last week of September 1955 by the Planning Commission for the purpose of assessing the extent of the problem of unemployment among educated persons in the country and for working out schemes which would help tackle the problem. The terms of reference were :- (i) To assess generally the extent of unemployment of the educated classes in the country and with special reference to conditions prevailing in areas where the problem is acute; (ii) To indicate the scope for special programmes for increasing employment opportunities for educated persons in the schemes that are being formulated by State Government and Central Ministries and in the private sector; (iii) To recommend special measures and programmes of training, re-orientation and implement which may facilitate the absorption of educated Unemployed persons into the economy of the country;
Government of India Planning Commission